Activities of Garenoxacin against Quinolone-Resistant Streptococcus pneumoniae Strains In Vitro and in a Mouse Pneumonia Model - Azoulay-Dupuis, E. (American Society for Microbiology, 2004)
Garenoxacin is a novel des-F(6) quinolone with enhanced in vitro activities against both gram-positive and gram-negative bacteria. We compared the activity of garenoxacin with that of trovafloxacin (TVA) against Streptococcus pneumoniae, together with their efficacies and their capacities to select for resistant mutants, in a mouse model of acute pneumonia. In vitro, garenoxacin was more potent than TVA against wild-type S. pneumoniae and against a mutant with a single mutation (parC), a mutant with double mutations (gyrA and parC), and a mutant with triple mutations (gyrA, parC, and parE). Swiss mice were infected with 10(5) CFU of virulent, encapsulated S. pneumoniae strain P-4241 or its derived isogenic parC, gyrA, gyrA parC, and efflux mutants and 10(7) CFU of poorly virulent clinical strains carrying a parE mutation or gyrA, parC, and parE mutations. The drugs were administered six times, every 12 h, beginning at either 3 or 18 h postinfection. The pulmonary pharmacokinetic parameters in mice infected with strain P-4241 and treated with garenoxacin or TVA (25 mg/kg of body weight) were as follows: maximum concentration of drug in serum (C(max); 17.3 and 21.2 μg/ml, respectively), C(max)/MIC ratio (288 and 170, respectively), area under the concentration-time curve (AUC; 48.5 and 250 μg · h/ml, respectively), and AUC/MIC ratio (808 and 2,000, respectively). Garenoxacin at 25 and 50 mg/kg was highly effective (survival rates, 85 to 100%) against the wild-type strain and mutants harboring a single mutation. TVA was as effective as garenoxacin against these strains. TVA at 200 mg/kg and garenoxacin at 50 mg/kg were ineffective against the mutant with the parC and gyrA double mutations and the mutant with the gyrA, parC, and parE triple mutations. The efficacy of garenoxacin was reduced only when strains bore several mutations for quinolone resistance.